Design and structural characterization of 2-methyl 8-hydroxyl quinolinilium 5-chloro salicylate salt. Issue 1 (22nd November 2021) - Mekala, R.; Mathammal, R.
Abstract: The enhanced physico chemical properties of 2-methyl 8-hydroxy quinolone was observed by the modified 2-methyl 8-hydroxy quinolinium 5-chloro salicylate crystal structure which were grown by slow evaporation method. The crystal structure was confirmed by single X-ray diffraction analysis. Crystal structure was stabilized through halogen bond interaction in the title crystal. The 3D Hirshfeld surfaces and the associated 2D fingerprint plots were investigated for intermolecular hydrogen bonding interactions. FTIR and FT-Raman spectral studies were characterized to reveal the presence of functional groups in the grown crystal. The proton and carbon chemical shift of the title compound were observed by 1 H and 13 C NMR analysis. Excited energy of the title compound was observed using UV-Visible spectral analysis. The fluorescence solid and solvent spectrum revealed that the green emission was observed in the grown crystal. The melting behavior and stability of the title compound was performed by TGA-DSC analysis. The ability to show the pharmacological behavior of the title crystal was analyzed by anti-oxidant, anti-microbial and anti-cancer studies.